DIAGNOSTIC ASSESSMENT AS AN EQUITY-ORIENTED PRACTICE: FICTION-BASED DEEP LEARNING FOR CULTURALLY AND SOCIALLY DIVERSE ELEMENTARY SCHOOL LEARNERS - Sujinah Sujinah; Dian Karina Rachmawati; Henry Trias Puguh Jatmiko; Alvenita Putri Aulia; Mahesa Ishak Ramdhani; Bouchra Aboura (Universitas PGRI Sumatera Barat, 2026)
In classrooms characterized by cultural and social diversity, diagnostic assessment is essential for determining students' academic preparedness and influencing how learners' identities are acknowledged or overlooked in educational decision-making. This research investigates cognitive and non-cognitive diagnostic assessment as practices aimed at equity within fiction-based deep learning, rooted in culturally responsive teaching (CRT) at the elementary school level. Employing a sequential mixed-methods approach, the study included validation of the assessment tool by experts and teachers, followed by pilot testing with 25 fifth-grade students from diverse cultural backgrounds. The cognitive assessment focused on understanding fictional texts, while the non-cognitive assessment examined students' learning preferences to gain insights into differences in affective and engagement aspects. The findings indicate significant differences in students' cognitive profiles and non-cognitive inclinations, highlighting the dangers of standardized instruction that disregards cultural differences, experiences, and identities. By incorporating culturally relevant fictional texts, diagnostic tools can more accurately reflect students' meaning-making processes, especially for those whose cultural experiences are often underrepresented in standardized assessments. However, the results also highlight the limitations of the instruments in eliciting high-level, critical responses, suggesting a need for more open and reflective assessment formats. This study adds to the research on culturally responsive assessment by redefining diagnostic testing as a pedagogical tool for inclusion rather than mere categorization. It offers practical implications for creating fiction-based immersive learning experiences that affirm students' identities, support differentiated instruction, and reduce the marginalization of culturally minoritized students. Future research should build on this work by using longitudinal and participatory methods that emphasize students' voices and sociocultural context.